Gallery Shimada Yamaguchi. - Nanjo, Fumio; Kondo, Yukio; Schrenk, Klaus (Yamaguchi : Gallery Shimada)
Sauer, Michel ; Johnston, Alan ; Horvat-Morvai, Bela ; Auberger, Pidder ; Shirakawa, Yoshio ; Hafner, Jonas ; Nishikawa, Katsuhito ; David Christian, Abraham ; Mars, Ton ; Partenheimer, Jürgen, Struth, Thomas ; Messina, Vittorio ; etc.
Japans & Engels
kunstcatalogus